2019
DOI: 10.1007/s13320-019-0533-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Silicon and Blue Phosphorene/MoS2 Hetero-Structure Based SPR Sensor

Abstract: Surface plasmon resonance (SPR) sensor based on the blue phosphorene/MoS 2 hetero-structure is presented to enhance the performance parameters, i.e., sensitivity, detection accuracy, and quality factor. The blue phosphorene/MoS 2 hetero-structure works as an interacting layer with the analyte for the enhancement of the sensitivity of the sensor. It is observed that the sensitivity of blue phosphorene/MoS 2 based sensor (i.e., structure-II) is improved by 5.75%, from the conventional sensor (i.e., structure-III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…In addition, because the monolayer of BlueP and TMDCs have the same hexagonal crystal structure, it is easy to construct the heterstructure of BlueP/TMDCs [40]. Srivastava obtained the SPR sensor of BlueP/MoS 2 heterostructure to improve the sensitivity [41]. Sharma et al proposed to use the BlueP/TMDCs molybdenum disulfide heterostructure, and compared with the traditional graphene SPR sensors [42].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because the monolayer of BlueP and TMDCs have the same hexagonal crystal structure, it is easy to construct the heterstructure of BlueP/TMDCs [40]. Srivastava obtained the SPR sensor of BlueP/MoS 2 heterostructure to improve the sensitivity [41]. Sharma et al proposed to use the BlueP/TMDCs molybdenum disulfide heterostructure, and compared with the traditional graphene SPR sensors [42].…”
Section: Introductionmentioning
confidence: 99%
“…However, when sensing structure works in the visible region [32–34] (633 nm incident light wavelength) the relative sensitivity obtained as 68.52°/RIU, which is greater than the previous case. Sensitivity enhancement is directly related to the metal nature having a complex refractive index.…”
Section: Resultsmentioning
confidence: 83%
“…Table 2 contains detailed investigation data to optimise the metal as well as dielectric layer thickness. It is found that for 3 nm of Au, 2 nm of Ag, and 10 nm of dielectric layer thickness, minimum reflectance (Rmin = 0.00129) is obtained along with the highest sensitivity of 59.64°/RIU (refer to Figure 3) However, when sensing structure works in the visible region [32][33][34] (633 nm incident light wavelength) the relative sensitivity obtained as 68.52°/RIU, which is greater than the previous case. Sensitivity enhancement is directly related to the metal nature having a complex refractive index.…”
Section: Thickness Optimization and Incident Light Wavelengthmentioning
confidence: 71%
“…The most frequently used setup for plasmon excitation is the Kretschman's configuration [11] where resonance is realised by the maximum dip in SPR angle with respect to the reflection intensity (RI) [12]. Here, we have taken the angle interrogation case [13] for a fixed wavelength of incident light source. In present scenario and requirement, the improved value of performance of SPR‐based biosensor is a major issue for research.…”
Section: Introductionmentioning
confidence: 99%
“…In present scenario and requirement, the improved value of performance of SPR‐based biosensor is a major issue for research. Theoretical analysis and literature survey show that SPR biosensor performance can be enhanced by the implementation of two‐dimensional (2D) [13, 14], transition metal dichalcogenides (TMDs) [15], 2D/TMD heterostructures [16, 17] or Perovskite materials [18, 19] in conventional metal prism‐based biosensor. In this study, we numerically demonstrate the functionality of the SPR based on combined structure of nano‐films [20] of WS 2 /BaTiO 3 /Black phosphorus and demonstrate improved sensitivity to bio sample as compared to conventional SPR sensor based on Ag layer.…”
Section: Introductionmentioning
confidence: 99%